Goliat Sang Pahlawan Filistin: Re-Reading 1 Samuel 17 Dalam Perspektif Pascakolonial - Oktovionaldi Bala Limbong (Vox Dei: Jurnal Teologi dan Pastoral, 2024)
The fight between David and Goliath is a metaphor used to describe the unequal confrontation between a small power and a large power. This fight shows David's courage and resilience amidst physical injustice and an imbalance of power. As a result, Goliath is depicted as a strong figure because he has a large body, while David is the opposite. This stereotype influences the perception of men with large bodies. This research seeks to discuss the stigma of masculinity experienced by men who have large bodies. Masculinity, even hypermasculinity, is sometimes a stigma attached to the self-image of large men who convey an aggressive and oppressive impression. For men with large bodies, the result of patriarchal standards becomes gender violence which also paralyzes men. Departing from postcolonial criticism which emphasizes the relationship between domination and subordination, this article examines and re-question the reader's position in seeing the character Goliath affected by the stigma of masculinity in his battle with David. Through text analysis methods, the author tries to reconstruct the reading of 1 Samuel 17 by describing the battle of Goliath, the champion of the Philistines, with David who represented the Israelites. This article finds that Goliath's large body was not his strength, but rather a source of weakness. In this way, this article breaks down the stigma of hypermasculinity attached to large men. Awareness of violence that does not look at gender, presents an inclusive reading full of new meaning for Goliath, the reader and the current context.